Application of TPM Tools in an Automotive Battery Assembly Line - Castillo-Revelo, A. S.; Manuico-Salas, L. C.; Maradiegue-Tuesta, F.; Alvarez-Merino, J. C. (IEEE International Conference on Industrial Engineering and Engineering Management, 2019)
This study sets out to increase the overall efficiency of equipment in the automotive battery assembly line by reducing the number of non-compliant products. To this end, the root cause analysis was performed, and it determined that disconformities are caused by the lack of standardization of processes, paucity of working methods, and inadequate maintenance plans. The proposal of this study involves the use of total productive maintenance (TPM) tools as the modal analysis of failures and effects, self-maintenance, and planned maintenance based on reliability-centric maintenance (RCM). The joint use of these tools leads to an increase in the quality of automotive batteries. The application of TPM and RCM is subject to internal and external factors affecting a company. The proposed methodology can be applied to small and medium-sized manufacturing industries with different production lines. As a result of its application, the number of non-compliant batteries was reduced by 30%, machine efficiency increased by 3.00%, and the mean time between failures was reduced by 19.96%.